FINDING #1 STOCKS : Screening, Backtesting, and Time-Proven Strategies - Matras, Kevin; Zacks Investment Research (Firm). (Hoboken, New Jersey : Wiley, 2011)
'Based on Zacks' Research Wizard product, this book will provide readers with market beating stock selection techniques and advice on how to build their own stock selection system. Derived largely from Zacks' Research Wizard home study course, the book will disclose several Zacks trading methods that have outperformed the market for a long period of time. In addition, the book will show readers how to screen stocks and develop selection criteria to build various types of stock portfolios, such as an aggressive growth; growth and income; momentum; and value. The book will include a 30-day free subscription to Zacks Research Wizard software'--
Includes index.
Keywords: Stocks; Investments; Investment analysis